Resource-Use Efficiency in Milk Production in Malwa Region of Madhya Pradesh - Sharma, Sandeep Kumar; Malhotra, Ravinder; Mahajan, Sumit (Indian Journal of Dairy Science, 2014)
The study conducted in Indore and Rajgarh districts of Malwa region of Madhya Pradesh collecting data from 160 milk producing households revealed that resource-use efficiency of green fodder for all types of dairy animals was found to be negative and significant indicating overutilization of this input which could be due to the fact that data was collected in winter season when plenty of green fodder was available. Therefore, reduced use of green fodder for all the dairy animals will not affect milk production adversely during that particular period. The concentrates were being underutilized in case of local cows while they were overutilised in case of buffaloes which calls for re-allocation of concentrates from buffaloes in favour of local cattle which will increase the milk production without spending more on concentrates. The concentrates were optimally used in case of crossbred cattle. The Cobb-Douglas production function was found best fit keeping in view sign, significance of regression coefficients and value of R2.